HBR guide to delivering effective feedback - Harvard Business Review (Boston Harvard Business Review Press., 2016)
To help your employees meet their goals and fulfill their potential, you need to provide them with regular feedback. But the prospect of sharing potentially negative news can be overwhelming. How do you construct your message so that it?s not only well received but also expressed in a way that encourages change?
Keywords: Employee retention